Restorative treatment in patient with Williams Syndrome: case report - Alessandra RECH; Isadora Caron RINALDI; Tatiane MAREGA (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT In Dentistry, any user with one or more limitations, of temporary or permanent mental nature, of physical, sensory, emotional or medical growth, is considered to be a Patient with Special Needs, preventing him from being subjected to a conventional dental situation. These patients form a group which may be considered at high risk for the development of oral diseases, according to the kind of pathogen. Among them, is the Williams-Beuren Syndrome, a rare congenital disease with cardiovascular involvement, mental retardation, dysmorphic face, idiopathic hypercalcemia, musculoskeletal problems, dental and growth anomalies. Familial and sporadic cases are thought to result from deletion of genetic material from adjacent genes located on the long arm of chromosome 7. This article reports a clinical case involving a four-year-old boy with Williams-Beuren Syndrome, referred to the clinic of the Specialization Course for Patients with Special Needs, at the São Leopoldo Mandic Dental Research Center, Campinas (SP). As the patient was resistant to dental care, in order to reduce anxiety and increase collaboration in clinical sessions, the Hixizine® medication was administered. For atraumatic restorative treatment and restorations, the following materials were used: Cleanjoy®, Futurabond DC®, Ionofil Plus® Grandioso®, Grandio® and Profluorid®. As result, it was possible to reach a level of excellence using the indicated materials and specific protocols. Based on this work and the lived experience, it can be observed that these patients can receive welcoming dental care in specialized clinics.